ANALISIS IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TENTANG RELOKASI PASAR UNTUK MENINGKATKAN GOOD GOVERNANCE - Abd. Rohman; Soleman Renda Bili; Asih Widi Lestari (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
The market relocation policy aims that better and cleaner city arrangement because in fact the presence of aninappropriate market raises several fundamental problems such as a narrow, less strategic market location,its proximity to gas stations, and traffic congestion. Unfortunatelly, many problems happen because of policiesregarding market relocation implementation. This study uses a quantitative approach with the technique ofdetermining informants using purposive sampling. Data collection techniques using interviews, observation anddocumentation. Data analysis was using data reduction techniques, data presentation and drawing conclusions.The results showed that the market relocation policy implementation was carried out through the socialization,structuring and controlling stages. However, in the relocation implementation, there are some traders whoreturn to the old market. The neglect of the lack of compliance by some traders raises the assumption thatthe Regional Government is inconsistent in implementing the policies that have been issued. Judging from theprinciples of good governance, the local government where the research was conducted has only applied threeprinciples, namely participation, transparency and accountability. The research results also show that the lackof facilities and infrastructure, low compliance of traders and the impression of inconsistency of the governmentin implementing policies that have been issued are the obstacles of these policies implementation.